Modification of substrate and product transport systems in Klebsiella pneumoniae to improve 1, 3-propanediol production. Issue 1 (22nd June 2022) - Teng, Yu; Guo, Chao; Xie, Mengmeng; Feng, Ao; Lu, Xinyao; Zong, Hong; Zhuge, Bin
Abstract: Substrate uptake and product export are important for microbial growth and product synthesis. Here, the glycerol uptake facilitator (GlpF) and the members of the resistance-nodulation-cell division (RND) type efflux system were overexpressed in Klebsiella pneumoniae to promote 1, 3-propanediol (1, 3-PDO) production. Overexpression of the endogenous K. pneumoniae GlpF improved glycerol dehydratase (GDHt) activity and promoted 1, 3-PDO titer from 55.6 to 65.1 g/l. RND members AcrA and the AcrE had no impact on 1, 3-PDO production. RND members AcrF and the TolC increased 1, 3-PDO titer from 55.6 to 68.4 g/l and 65.4 g/l, respectively. MexB significantly decreased GDHt activity and 1, 3-PDO titer. Notably, MexF dramatically enhanced GDHt activity and promoted 1, 3-PDO titer and glycerol conversion rate to 74.0 g/l and 0.62 mol/mol, respectively. However, coexpression of the endogenous GlpF and MexF did not further improve 1, 3-PDO production. The results present here provided novel information about the applications of the uptake of glycerol and the efflux of 1, 3-PDO. Abstract : The glycerol uptake facilitator (GlpF) and the members of the resistance-nodulation-cell division (RND) type efflux system were overexpressed in Klebsiella pneumoniae to promote 1, 3-propanediol (1, 3-PDO) production.